The Influence of Fraud Hexagon Theory on Detecting Fraudulent Factors in Financial Reports of State-Owned Companies Listed on the IDX 2018-2022 - Aulia, Dina; Masrullah; Zulaeha, Sitti (Universitas Muhammadiyah Jember, 2024)
Financial statement fraud is a paradigm that often occurs in Indonesia and causes many losses. Therefore, the aim of this research is to detect the emergence of potential fraud in financial reports using the hexagon fraud theory. In the hexagon fraud theory, there are six dominant factors that can trigger fraud in financial reports: pressure, opportunity, rationalization, ability, arrogance, and collusion. Pressure is proxied by financial targets, financial stability, and financial need; opportunity is proxied by the nature of industry and ineffective monitoring; rationalization is proxied by a change auditor as a proxy for capability to become and change in director; arrogance is proxied by political connections and the frequent number of CEOs; and collusion is proxied by projects with the government. In this research, the dependent variable is measured using the Jones model. The purposeful sampling technique was used in this research in order to obtain a population sample with the criteria of state-owned companies listed on the Indonesia Stock Exchange during the last 5 years, namely, 2018–2022. The quantitative method is supported by multiple regression analysis techniques using the SPSS 26 analysis tool in this research. The results of this research show that the variables financial target, financial stability, personal financial need, nature of industry, ineffective monitoring, change in auditor, change in directors, and political connection have no influence on the potential for fraudulent financial statements. Frequent CEO pictures and collaboration projects with the government have a positive and significant effect on the potential for fraudulent financial statements